Hematite Fe2O3@nitrogen-doped graphene core-shell photocatalyst for efficient cephalexin degradation under visible light irradiation. Issue 23 (1st December 2022) - Van Dao, Dung; Ngoc Bich, Tran Thi; Thu Ha, Nguyen Thi; Wang, Wenmeng; Kim, Taehwan; Kim, Hooyeon; Khanh Duy, Pham Huynh; Ha, Nguyen Ngoc; Thuy Van, Do Thi; Lee, In-Hwan
Abstract: Recently, photocatalysis has been a promising technology for removing pharmaceutical antibiotics due to low energy utilization and cost-effectiveness. In this study, hematite Fe2 O3 was encapsulated with nitrogen-doped graphene to produce an active and stable Fe2 O3 @NGr core-shell flatform for photocatalytic degradation of cephalexin. Fe2 O3 @NGr under visible light irradiation delivered an impressive cephalexin degradation efficiency of 90% within 60 min, superior to free-standing Fe2 O3 (40%) and NGr (15%) species, respectively. Also, it could bring a lasting catalyst for light-driven cephalexin removal. The improvements were synergistically attributed to two following effects. First, the facile generation and transfer of electron-hole pairs in the Fe2 O3 @NGr core-shell design were achieved under visible light. Second, the active surface of NGr shell weakly bound to the CO gas as a central intermediate species in the decomposition by-products, speeding up the cephalexin removal. Thus, these two basic factors provided mechanistic insights into the working of Fe2 O3 @NGr core-shell system in terms of cephalexin degradation under visible light.